Why combating tobacco smuggling is a priority. (9th October 2008) - West, Robert; Townsend, Joy; Joossens, Luk; Arnott, Deborah; Lewis, Sarah
Abstract : Robert West and colleagues argue that reducing the amount of tobacco smuggled into the UK might prevent substantial numbers of premature deaths